PERANCANGAN UI/UX WEBSITE FURLOVE UNTUK MENGOPTIMALKAN KEMUDAHAN PEMESANAN JASA PERAWATAN HEWAN PELIHARAAN - Rani Artika Sari; Fitra Zaelani; Aisyah Nushrah Diniyyati; Sari Armiati (CV. Denasya Smart Publisher, 2026)
The UI/UX design of the FurLove website aims to optimize the ease of booking pet care services, addressing common problems such as lack of transparent information and complicated processes on the service booking platform. This study uses the Design Thinking method, including the stages of Empathize, Define, Ideate, Prototype, and Test. The Empathize stage involves distributing questionnaires to 17 respondents to identify pain points such as difficulty finding information and making reservations. In the Define stage, 10 features were tested using the KANO method to prioritize user needs. The